COMPARISON OF ZIEHL-NEELSEN, KINYOUN’S AND FLUORESCENT STAINING FOR DETECTION OF MYCOBACTERIUM TUBERCULOSIS IN SPUTUM SAMPLES BEFORE AND AFTER PETROFF’S CONCENTRATION TECHNIQUE - P, Neelu Sree; J, Terin; Dutta, Himadri; M, Kalyani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of the study were to find out the presence of Mycobacterium tuberculosis in sputum samples using Ziehl-Neelsen (ZN), Kinyoun’s, and (auramine) fluorescent staining and to compare the three staining techniques with and without Petroff’s concentration and to find out the most preferable staining of M. tuberculosis. Methods: Sputum sample was collected and concentrated by 4% NaOH (Petroff’s concentration). Microscopic examination of the sample was done before concentration and after concentration by ZN staining, Kinyoun’s staining, and fluorescent staining (Auramine). Grading of acid-fast bacilli (AFB) by three staining was done before and after concentration according to RNTCP guidelines. Results: Total of 452 sputum samples were collected and subjected to microscopy examination by ZN, Kinyoun’s, and fluorescent staining methods to compare the presence or absence of AFB with or without concentration. Among the 452 sputum samples, total of 67 (15.6%) sputum samples were positive for the presence of AFB. Majority 40.3% (n=21) of TB positive patients were observed in the age group 51â€“60 years. The results of Auramine-O staining showed positive diagnoses in 15.9% of the samples; sensitivity was 100% and specificity 95.6%. Conclusion: The use of fluorescent staining significantly increases the diagnostic value of the smear, particularly where there are low-density bacilli which may escape detection on ZN stained smears.